Associations Between Blood Hemoglobin Concentrations and Cardiometabolic Risk in Middle-Aged Women - Tazuko Tokugawa; Akihiro Sawada; Satoshi Higasa; Ichiro Wakabayashi (Women's Health Reports)
Objective: Patients with polycythemia have a high risk of thrombo-atherosclerotic diseases. However, it remains to be clarified whether a high blood hemoglobin level is related to cardiometabolic risk in women. Methods: The overall subjects were 18,410 middle-aged women who had received health checkup examinations at their workplaces. The subjects were divided into four groups of quartiles for hemoglobin levels. Cardiometabolic risk factors were compared in the four quartile groups. Individuals showing abnormally low hemoglobin levels (less than 11.0 g/dL) and/or having a history of therapy for anemia (n = 3,690) were excluded from the study. Results: The prevalence of polycythemia (hemoglobin: higher than 16.0 g/dL) was 0.14%. Body mass index, waist-to-height ratio, blood pressure, triglycerides, LDL cholesterol, and hemoglobin A1c were significantly higher in the highest quartile group of hemoglobin than in the lowest quartile group and tended to be higher with an increase of the quartile. Odds ratios of the highest versus lowest quartile groups of hemoglobin were 2.64 (2.25–3.10) for high LDL cholesterol/HDL cholesterol ratio, 3.05 (2.69–3.46) for high lipid accumulation product, 2.26 (2.05–2.50) for high cardiometabolic index, and 3.71 (3.07–4.47) for metabolic syndrome. Conclusions: Although the prevalence of polycythemia was very low, cardiometabolic risk was higher in those showing relatively high hemoglobin levels than in those with lower levels. Therefore, normal high blood hemoglobin is suggestive of increased cardiovascular risk in middle-aged women.